KINERJA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA DALAM MEWUJUDKAN PEMBERDAYAAN MASYARAKAT MELALUI PENGGUNAAN DANA DESA DI KABUPATEN BELU PROVINSI NUSA TENGGARA TIMUR - Maximilianus Mario Taek; Sadu Wasistiono; Meltarini Meltarini (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2020)
The use of Village Funds is not appropriate and there are still problems so that it has not reduced the poverty rate, this is because the guidance is not maximized by the Belu Regency PMD Office. This study aims to analyze performance of the Community and Village Empowerment Service in realizing community empowerment through the use of Village Funds. The theory used is the performance of Sinambela Lijan (2012), with indicators of productivity, responsiveness, responsibility and accountability. The approach to data analysis is the SWOT analysis with the Litmus test. This study used qualitative research method with descriptive approach, data collection techniques: interviews (17 informants) and documentation. The findings of the study indicate that human resource capacity is still low, infrastructure is still limited, lack of cross-sectoral coordination, lack of community understanding and weak institutional capacity in the village. Conclusion: The performance of the Community and Village Empowerment Service is quite good, but there are still some problems so that the authors convey several strategic issues, namely increasing the capacity of employees as trainers and facilitators so that community empowerment is more effective and maximizes the potential in the village so that it can be used to support community empowerment activities, with the aim of realizing Village independence. Keywords: Performance, Village Funds, Community Empowerment